Early psoriatic arthritis: short symptom duration, male gender and preserved physical functioning at presentation predict favourable outcome at 5-year follow-up. Results from the Swedish Early Psoriatic Arthritis Register (SwePsA). Issue 2 (25th January 2013) - Theander, Elke; Husmark, Tomas; Alenius, Gerd-Marie; Larsson, Per T; Teleman, Annika; Geijer, Mats; Lindqvist, Ulla R C
Abstract : Objective: The Swedish Early Psoriatic Arthritis Register describes the course of early psoriatic arthritis (PsA) in a real life clinical setting in Sweden. The aim of this study was to obtain information on predictors of clinical outcomes over a 5-year period with special focus on effects of gender, joint patterns, diagnostic delay and initial disease activity. Methods: In six centres, patients with signs suggestive of PsA were included in the Swedish Early Psoriatic Arthritis Register within 2 years of symptom onset. CASPAR (classification for psoriatic arthritis) criteria were fulfilled by 197 patients who had passed the 5-year follow-up. Disease activity was measured by the Disease Activity Score including 28 joints (DAS28) and the Disease Activity Index for Psoriatic Arthritis (DAPSA). Remission and minimal disease activity (MDA) were used as outcome measures. Results: Mean age at inclusion was 46 years, younger in male than female patients (43 vs 48 years). Mean DAS28 was 3.7 and 3.0 at inclusion and 2.8 and 2.1 at follow-up for women and men, respectively—significantly higher in women at both visits. Likewise, DAPSA scores were significantly higher in women. The degree of improvement (change in DAS28 and DAPSA) was similar. Men achieved MDA or remission (50% vs 33%, 25% vs 13%, respectively) more often, and women had significantly more polyarthritis at inclusion (49% vs 27%) and after 5 years (25% vs 15%). Axial or mono/oligoarticular disease was predominant in men. Independent predictors of MDA at the 5-year follow-up were: shorter symptom duration; greater general well-being (global visual analogue scale); and low Health Assessment Questionnaire at inclusion. Conclusions: In early PsA, short delay between onset of symptoms and diagnosis, preserved function, and male gender are the most important predictors of favourable clinical outcome at the 5-year follow-up. Early recognition of PsA and active treatment may be important, particularly in women with polyarticular disease.